P906 Prevalence and CARD9 IBD risk variant rs4077515 in a Chilean IBD Cohort. (30th January 2023) - Pérez, T; Bustamante, M L; Magne, F; Alvares, D; Álvarez-Lobos, M; Hernandez-Rocha, C; Aguliar, N; Azocar, L; Baez, P; Zazueta, A; Estela, R; Escobar, S; et al.
Abstract: Background: Genome-wide association studies (GWAS) have identified hundreds of polymorphisms associated with an increased risk of developing IBD. Among risk genes identified by GWAS, CARD9, a gene encoding an adapter molecule involved in the innate immune response to fungi and bacteria, has been related to IBD risk. CARD9 alleles in IBD patients may have either a protective function or a high genetic risk factor such as rs4077515. Interestingly, the CARD9S12N (rs4077515) variant has a higher frequency in the Latin South American population than the Caucasian population. The relevance of rs4077515 in the risk of IBD in the Latino population is unknown. Aims: (1) To estimate allele and genotype frequencies for rs4077515 in IBD patients and Chilean controls and compare with Ensembl genome database (public data available). (2) To compare the allele and genotype distributions in IBD patients and controls, including association tests and estimation of ORs according to additive, dominant and recessive penetrance models. Methods: 260 IBD patients were genotyped using the TaqMan SNP genotyping technology based on qPCR. Aggregated genotype information for 3147 population-based Chilean controls was retrieved from a published study on gallstones in Chileans (Lorenzo et al., Hepatology 2021). We calculated the allele and genotype frequencies for rs4077515 and then compared these frequencies with controls. A Chi-square test of association was used under the null hypothesis of no association between genotypes and disease. Univariate and multiple logistic regression were performed (additive, dominant, and recessive penetrance models). Results: Table 1 compares rs4077515 allele and genotype frequencies in Chileans and other populations (Ensembl data set). Table 2. exhibits the estimated odds ratio for IBD, CD, and UC in Chilean population. Table 3. reveals the association results for rs4077151 models in the Chilean population. Conclusion: In this study, the A risk allele for rs4077515 is significantly more frequent in the Chilean population than reported in other populations such as European, but similar to Amerindian. In this Chilean cohort, the variant rs4077515 is not associated with higher IBD risk. However, this could be an effect of sample size, or patients carrying rs4077515 requires an additional factor to IBD development.